Analysis of the effect of neuroendoscopy-assisted microscopy in the treatment of Large (Koos grade IV) vestibular schwannoma - Yang, Zhenxing; Xiong, Xiaoxing; Jian, Zhihong; Du, Li (Frontiers in Oncology, 2023)
Introduction This article aimed to investigate the effects of the endoscopic-assisted microsurgery technique on the resection of large (Koos grade IV) vestibular schwannoma (VS) and provide a prognosis analysis of the patients. Methods A retrospective analysis of the use of the endoscopic-assisted microsurgery technique in 16 cases of large vestibular schwannoma surgery was carried out. Intraoperative nerve electrophysiological monitoring was conducted to explore the effect of neuroendoscopy on the resection of internal auditory canal tumors, protection of the facial nerve, and minimizing postoperative complications. Results Tumors were completely removed in all 16 cases, and the facial nerve was anatomically preserved in 14 cases (87.5%). There was no postoperative cerebrospinal fluid leakage and no intracranial infection complications occurred.Following the House-Brackmann (H-B) grading system, post-operative facial nerve function was grade I in 5 cases, grade II in 6 cases, grade III in 3 cases, and grade V in 2 cases. As a result, the preservation rate of facial nerve function (H-B grade I-II) was 68.8%. All 16 patients were followed up for 3 to 24 months, and no tumor recurrence was found on enhanced MRI. Discussion Using the endoscopic-assisted microsurgery technique in the retrosigmoid approach has many advantages over the microscopic-only approach. When compared to the microscopy-only approach, the endoscope can provide a wide-angle surgical field superior to that of a microscope in areas such as the internal auditory canal in the resection of large VS, minimize iatrogenic injuries, ensure complete removal of internal auditory canal tumors, and well as reducing postoperative complications such as cerebrospinal fluid leakage and the loss of facial and auditory nerve functions.